The Influence of Islamic Branding , Religiousity, and Fashion Trends on Islamic Fashion Purchase Decisions - Fahrullah, Arasy; Zulfa, Fina Lailiz; Anwar, Moch. Khoirul; Ridlwan, Ahmad Ajib; Yasin, Ach. (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This study aims to investigate the influence of Islamic branding, religiosity, and fashion trends on the purchasing decisions of Islamic fashion among students in Surabaya. The research employs a quantitative approach with multiple linear regression analysis techniques. Primary data was collected through questionnaire distribution. The research sample consisted of 100 randomly selected respondents based on specific criteria using purposive sampling techniques. The results indicate that Islamic branding and fashion trends partially influence the purchasing decisions of Islamic fashion, while religiosity does not have a partial effect on purchasing decisions. The coefficient of determination testing results show that Islamic branding, religiosity, and fashion trends collectively account for 50.2% of the variance in purchasing decisions for Islamic fashion. This study can provide insights for businesses to develop more effective marketing strategies. These findings underscore the importance of additional factors such as product quality, lifestyle, price, and the role of celebrities and influencers in future research.